1985
DOI: 10.1152/ajpregu.1985.249.4.r379
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary isolation of mosquito natriuretic factor

Abstract: A natriuretic factor that triggers diuresis in isolated Malpighian tubules of the mosquito was isolated from the head of the yellow-fever mosquito Aedes aegypti by passing a saline extract of mosquito heads through low-pressure and then high-pressure liquid chromatography (HPLC) columns. Three fractions with biologic activity eluted during a reverse-phase HPLC linear acetonitrile gradient run. Fraction I depolarized the transepithelial voltage (Vt) of isolated perfused Malpighian tubules but did not not stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
47
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 0 publications
4
47
0
Order By: Relevance
“…In A. aegypti, several diuretic peptides have been found that are released to the haemolymph by the central nervous system (Jagge and Pietrantonio, 2008;Beyenbach et al, 2010). Shortly after the onset of a blood meal the natriuretic peptide appears in the haemolymph (Petzel et al, 1985;Wheelock et al, 1988), followed by further peptides that have a non-selective diuretic effect (Coast, 2009). The natriuretic peptide, previously referred to as mosquito natriuretic peptide (MNP) (Petzel et al, 1985) and now known to be the calcitonin-like peptide Anoga-DH 31 , increases the secretion of NaCl-rich fluid in isolated tubules of A. aegypti severalfold (Petzel et al, 1985;Coast et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In A. aegypti, several diuretic peptides have been found that are released to the haemolymph by the central nervous system (Jagge and Pietrantonio, 2008;Beyenbach et al, 2010). Shortly after the onset of a blood meal the natriuretic peptide appears in the haemolymph (Petzel et al, 1985;Wheelock et al, 1988), followed by further peptides that have a non-selective diuretic effect (Coast, 2009). The natriuretic peptide, previously referred to as mosquito natriuretic peptide (MNP) (Petzel et al, 1985) and now known to be the calcitonin-like peptide Anoga-DH 31 , increases the secretion of NaCl-rich fluid in isolated tubules of A. aegypti severalfold (Petzel et al, 1985;Coast et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Shortly after the onset of a blood meal the natriuretic peptide appears in the haemolymph (Petzel et al, 1985;Wheelock et al, 1988), followed by further peptides that have a non-selective diuretic effect (Coast, 2009). The natriuretic peptide, previously referred to as mosquito natriuretic peptide (MNP) (Petzel et al, 1985) and now known to be the calcitonin-like peptide Anoga-DH 31 , increases the secretion of NaCl-rich fluid in isolated tubules of A. aegypti severalfold (Petzel et al, 1985;Coast et al, 2005). MNP acts via the second messenger cyclic AMP, and its diuretic effects can be duplicated by membrane-permeant cAMP analogues (Petzel et al, 1987;Coast et al, 2005;Beyenbach et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Because mammalian plasma (∼290 mOsm) is hypo-osmotic to the hemolymph (354 mOsm), the blood meal causes the hypo-osmotic expansion of the ECF . This is largely corrected by increasing the excretion of urine that is hypo-osmotic (309 mOsm) to the hemolymph Coast et al, 2005;Petzel et al, 1985;. Diuretic hormones that are released from the mosquito head during the ingestion of blood trigger this diuresis (Beyenbach, 2003b;Wheelock et al, 1988).…”
Section: The Ecf Of Insects Gorging On Fluidsmentioning
confidence: 99%
“…At least two diuretic hormones correct the ECF expansion in the first two post-prandial hours Beyenbach and Piermarini, 2011). One is the natriuretic hormone, a calcitonin-like peptide (Coast et al, 2005;Petzel et al, 1985Petzel et al, , 1986) that increases the Na + conductance of the basolateral membrane of principal cells, which increases the transepithelial secretion of Na + (Sawyer and Beyenbach, 1985). The stimulation of active transepithelial secretion of Na + hyperpolarizes the transepithelial voltage to more lumen-negative voltages, thus increasing the paracellular secretion of Cl − Beyenbach, 1983, 1984).…”
Section: The Ecf Of Insects Gorging On Fluidsmentioning
confidence: 99%
“…The different effects of these peptides across and even within orders should be noted. For example, the cockroach CT-like peptide Dippu-DH 31 has a nonselective effect on the Na + and K + ratio in the cockroach (Furuya et al, 2000) while Anoga-DH 31 , recently shown by Coast et al (2005) to be the previously uncharacterised natriuretic peptide of mosquitoes (Petzel et al, 1985), markedly increases [Na…”
Section: Effects Of Ct-like Peptides and Thapsigargin On Mealworm Tubmentioning
confidence: 99%